Conventional cytotoxic and novel therapeutic concepts in colorectal cancer. - Midgley, R; Kerr, D (2001)
Colorectal cancer (CRC) is a major cause of death, particularly in the Western world, leading to 400,000 deaths each year. Of the patients, 30% have advanced disease at presentation, either locally or at distant sites and chemotherapy in this setting has an established role in improving survival and palliating symptoms. In addition, approximately 50% of those patients initially believed to be cured by surgery, subsequently relapse and die of their disease. Adjuvant chemotherapy administered for six months after surgery for Dukes C colon cancer improves absolute survival by 5-10%. However, the role of adjuvant chemotherapy in Dukes B colon or Dukes B/C rectal tumours is still controversial and is only recommended within the scope of a randomised clinical trial. Cytotoxic drug development for colorectal cancer has traditionally followed the established pathway of Phase I, Phase II and then Phase III trials in advanced disease, with subsequent translation into the adjuvant setting. For the purpose of this review current conventional chemotherapy for advanced CRC is described, followed by an explanation of newer developments that are predicated upon our increasing understanding of the molecular processes underpinning malignant transformation, invasion and metastasis. Paradigm shifts in trial design necessitated by a mechanistic approach to drug development are also discussed.